Lead-acid battery electrolyte and application thereof

By adding surfactant to the electrolyte for lead-acid batteries, the problems of electrolyte layering and lead dendrites are solved, which extends the battery's cycle life and improves battery performance.

CN118899552BActive Publication Date: 2025-03-28TIANNENG BATTERY GROUP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411388903.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-03-28
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Valve-controlled sealed lead-acid batteries have electrolyte layering and lead dendrites short circuit problems in specific application scenarios, which seriously restrict the battery's circulation service life.

Method used

By adding surfactant, specifically sodium dodecyl sulfate and sodium dodecylbenzenesulfonate to the lead-acid battery electrolyte, the surface tension of the electrolyte is changed, the electrolyte layering phenomenon is slowed down, and stable complexes are formed by capturing lead ions in the electrolyte to avoid the formation of lead dendrites.

Benefits of technology

It effectively slows down the stratification phenomenon of electrolyte, reduces the risk of lead dendrites, thereby extending the recycling service life of lead batteries and improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118899552B_ABST
    Figure CN118899552B_ABST
Patent Text Reader

Abstract

The present invention discloses an electrolyte for a lead-acid battery and its application, and belongs to the technical field of lead-acid battery production. The present invention improves the electrolyte by adding a surfactant to change the surface tension of the electrolyte, which can slow down the stratification of the electrolyte from the source. At the same time, the introduced surfactant captures lead ions in the electrolyte to form a stable complex, avoids the formation of lead dendrites, and reduces the risk of short circuit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lead-acid battery production, and particularly relates to an electrolyte for a lead-acid battery and application thereof. Background Art

[0002] As an efficient and reliable energy storage device, valve-regulated sealed lead-acid battery (VRLA battery) has been widely used in power systems, UPS power supplies, railway systems, communication equipment and various emergency equipment. Its core advantage lies in its maintenance-free characteristics and long service life, which are largely attributed to the AGM (Absorbent Glass Mat) separator it uses. As a key component of VRLA battery, AGM separator not only has excellent acid corrosion resistance, high porosity and good insulation performance, but also can effectively fix the electrolyte and provide a hydrogen-oxygen recombination channel during the charge and discharge process, thereby realizing the maintenance-free function of the battery and improving the overall performance of the battery.

[0003] However, despite the excellent performance of AGM separators in VRLA batteries, their shortcomings gradually emerged in specific application scenarios, such as stationary use and deep cycle power batteries, significantly restricting the cycle life of the battery. The main problems are concentrated in two aspects: electrolyte stratification and lead dendrite short circuit.

[0004] 1. Electrolyte stratification problem

[0005] Electrolyte stratification is a common problem in VRLA batteries, especially under long-term operation or extreme conditions. Due to the influence of electrolyte surface tension and separator characteristics, the electrolyte density will be uneven along the height direction inside the battery, which is manifested as a significantly higher sulfuric acid content at the bottom than in the middle and upper parts. This stratification phenomenon leads to increased sulfation at the bottom of the positive and negative electrodes, damage to the positive electrode structure, and softening, while the sulfation of the negative electrode is more irreversible, ultimately leading to failure of the positive and negative electrodes and significant attenuation of the battery capacity.

[0006] The electrolyte stratification problem is currently being solved by adjusting the ratio of coarse and fine cotton in the separator formula. Increasing the proportion of fine cotton can enhance the separator's ability to resist stratification, but at the same time it will reduce the wet pressure and have a negative impact on the battery life. Therefore, manufacturers need to carefully balance the formula design to maximize the ability to resist stratification while maintaining a certain wet pressure. However, for thin separators with extreme designs, especially when the thickness is less than 0.50mm (100kPa), the electrolyte stratification problem is still severe, which seriously restricts the cycle life of the battery.

[0007] 2. Lead dendrite short circuit problem

[0008] Lead dendrite short circuit is another major challenge faced by VRLA batteries during long-term use. During the charge and discharge cycle, lead ions continue to dissolve and precipitate, and eventually aggregate into lead dendrites on the fibers inside the separator. As the number of cycles increases, lead dendrites may penetrate the separator, causing a micro short circuit between the positive and negative electrodes, which in turn causes a voltage drop and shortens the battery discharge time. For batteries with fixed uses, the risk of lead dendrite short circuit is higher due to long-term storage. Thin separators are more prone to micro short circuits during cycling due to their relatively low structural strength, further accelerating the decay of battery capacity.

[0009] To solve the problem of lead dendrite short circuit, the industry has adopted a variety of strategies, including controlling the discharge rate of the battery, adding additives to stabilize the electrolyte, and using external circuits to limit the growth of dendrites. However, these measures have limited effects in practical applications, especially for battery systems with long-term operation and high-intensity cycles, and more effective solutions still need to be further explored. Summary of the invention

[0010] Based on the deficiencies in the prior art, the present invention provides an electrolyte for a lead-acid battery and its application, by improving the electrolyte and solving the problems of electrolyte stratification and lead dendrite short circuit by adding a surfactant.

[0011] The specific technical solutions of the present invention are as follows:

[0012] An electrolyte for a lead-acid battery, the electrolyte for a lead-acid battery comprising sulfuric acid and an additive, wherein the additive comprises the following raw materials, based on the mass of the sulfuric acid: 0.5% to 1.0% of an inorganic salt and 0.05% to 0.20% of a surfactant;

[0013] Wherein, the inorganic salt is anhydrous sodium sulfate, and the surfactant is at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate.

[0014] Preferably, the mass fraction of the sulfuric acid is 31% to 35%. The sulfuric acid used in the present invention is obtained by diluting concentrated sulfuric acid, and the density of concentrated sulfuric acid is 1.83 g / cm 3 , the quality score is 98.3%.

[0015] Preferably, when the surfactant is sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, the mass ratio of sodium dodecyl sulfate to the surfactant is not less than 50%.

[0016] On the one hand, the surfactant adopts sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, and the effect of the two mixed additions is better than that of single use; on the other hand, after the surfactant is added in the chemical formation process, there will be foaming, and the foam will flow out, resulting in the loss of the amount of surfactant added, and seriously causing the consequence of short circuit. It is found in the experiment that the most critical control of the ratio of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate in the surfactant is to make the ratio of sodium dodecyl sulfate more, and the foaming can be controlled. Finally, the foaming phenomenon can also be controlled to a certain extent by controlling the amount of inorganic salt added and the voltage of the chemical formation.

[0017] The present invention also provides application of the lead-acid battery electrolyte in preparing lead-acid batteries.

[0018] Specifically, when the separator thickness of the lead-acid battery h<0.5mm, the added amount of the surfactant is not less than 0.1%; when the separator thickness of the lead-acid battery h≥0.5mm, the added amount of the surfactant is not higher than 0.18%.

[0019] Furthermore, the plate height is recorded as H, and the distance between the positive and negative plates is recorded as L.

[0020] Different battery performance requirements and different design parameters have different anti-stratification capabilities, and the batteries are differentiated from H and L.

[0021] H is the plate height. The height of H determines the capacity of the battery. H also determines the stratification phenomenon. The higher it is, the easier it is to stratify. L is the distance between the positive and negative plates. Obviously, the distance of L determines the thickness of the separator. The smaller L is, the thinner the separator is, the easier it is for dendrites to short-circuit. The less the base material of the separator is, the easier it is to stratify. In this case, fine cotton separators with good anti-stratification effect are usually selected, but if thinner separators are selected, fine cotton cannot solve the above problems and the price is more expensive. On the contrary, the thicker the separator, the more base material there is. Relatively speaking, coarse cotton separators can be used, but coarse cotton separators have a natural stratification disadvantage, and it is also necessary to consider reducing stratification from the electrolyte formula.

[0022] When designing a battery, H and L are actually two important parameters. Usually the battery will not be too short. If it is too short, the capacity will be difficult to achieve, so H will maintain a certain value, that is, the ratio of H / L. From this perspective, it depends on L. The larger the L, the smaller the H / L ratio, the wider the distance between the positive and negative, the less likely it is to have dendrite short circuits, it is easier to add acid, and it is easier to control the temperature, but the battery energy density will be lower.

[0023] The smaller L is, the narrower the distance between the positive and negative electrodes will be, the larger the value of H / L will be, the easier it will be for dendrites to short-circuit, and the temperature will be difficult to control. Therefore, the idea of ​​the present invention is to solve the problem of separator stratification by using electrolyte.

[0024] When the thickness of the separator of the lead-acid battery is h<0.5mm, when H / L>120, the added amount of the surfactant is not less than 0.15%; when H / L≤120, the added amount of the surfactant is less than 0.15%;

[0025] If the thickness of the separator is less than 0.5mm, it means that the separator base itself is very thin. As mentioned above, the anti-delamination separator cannot solve the problem. H / L>120, that is, L is very small. A 0.45mm separator is selected. In the experiment, in order to resist delamination and short circuit, the addition amount is not less than 0.15%, and the effect is better. H / L≤120, L is slightly larger, and the thickness of the separator is slightly larger. From the perspective of experimental effect and cost, the addition amount of surfactant is less than 0.15% which is optimal;

[0026] When the separator thickness of the lead-acid battery is h≥0.5mm, when H / L>120, the added amount of the surfactant is 0.15%~0.18%; when H / L≤120, the added amount of the surfactant is 0.05%~0.10%.

[0027] If the thickness of the partition is greater than 0.5mm, it means that the partition base itself is barely acceptable. Anti-delamination partitions can solve part of the problem, but the price of the partition will be much higher. In order to control the design cost, partitions of this thickness value are usually made of coarse cotton, and naturally the anti-delamination effect will be worse.

[0028] Therefore, H / L>120 means L is very small. For example, the thickness of the separator is 0.52mm. In the experiment, in order to resist delamination and short circuit, the addition amount is 0.15%~0.18%, and the effect is also good. H / L≤120, L is too large, the base thickness of the separator is completely OK, and delamination will also occur. However, from the perspective of experimental effect and cost, the addition amount of surfactant is 0.05%~0.10% to solve the problem.

[0029] Specifically, the method for preparing the lead-acid battery electrolyte comprises the following steps:

[0030] Sulfuric acid used in preparing the chemical;

[0031] The surfactant is added according to the separator thickness of the lead-acid battery, the plate surface height and the distance between the positive and negative plates, and then added into the prepared sulfuric acid, and then the inorganic salt is added to obtain the lead-acid battery electrolyte.

[0032] The specific steps include:

[0033] 1) Prepare dilute sulfuric acid according to the mass fraction of dilute sulfuric acid required for the batch of formation. The amount of dilute sulfuric acid is A (kg). Calculate the amount of concentrated sulfuric acid B (kg). Calculate the amount of pure water C (kg) required to prepare the dilute sulfuric acid. Weigh 0.8C (kg) of pure water and slowly add the weighed concentrated sulfuric acid B (kg). Set aside after the temperature drops.

[0034] 2) Weigh 0.2C (kg) of pure water, determine the addition ratio according to the design parameters of the batch of batteries (h and H / L), weigh the surfactant according to the mass A (kg) and dissolve it in pure water. The surfactant is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate alone, or a mixture of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate. When the two are mixed, the mass ratio of sodium dodecyl sulfate in the mixed sample is not less than 50%. Stir until the surfactant is completely dissolved in pure water and set aside;

[0035] 3) adding the surfactant solution prepared in step (2) above to the dilute sulfuric acid prepared in step (1) above;

[0036] 4) Finally, add a certain proportion of anhydrous sodium sulfate according to mass A (kg);

[0037] 5) Cool the prepared electrolyte to the temperature between 0℃ and 5℃ and set aside.

[0038] Set the acid adding volume of the acid adding machine according to the amount of electrolyte added to the batch of batteries to complete the acid adding.

[0039] After the acid is added, cool in a water cooling tank (water temperature below 20°C) for no less than 25 minutes.

[0040] After cooling, it flows into the formation tank and starts charging and formation.

[0041] Because surfactants are prone to foaming, when preparing lead-acid batteries, the formation current is controlled during the formation stage and the formation voltage does not exceed 16.5V to prevent foaming during the process and ensure the amount of surfactant added.

[0042] Beneficial effects of the present invention:

[0043] The present invention improves the electrolyte by adding a surfactant to change the surface tension of the electrolyte, thereby slowing down the stratification of the electrolyte from the source. At the same time, the introduced surfactant captures lead ions in the electrolyte to form a stable complex, thereby avoiding the formation of lead dendrites and reducing the risk of short circuit. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Lead dendrites in the AGM separator of battery No. 9 in Example 3.

[0045] Figure 2Lead dendrites in the AGM separator of battery No. 14 in Example 3.

[0046] Figure 3 This is the lead dendrite in the AGM separator of battery No. 1 in Example 4.

[0047] Figure 4 These are lead dendrites in the AGM separator of battery No. 7 in Example 4.

[0048] Figure 5 These are lead dendrites in the AGM separator of battery No. 4 in Example 5.

[0049] Figure 6 These are lead dendrites in the AGM separator of battery No. 7 in Example 5. DETAILED DESCRIPTION

[0050] Electrolyte configuration: During battery use, the sulfuric acid concentration is less than 31%. If the electrolyte concentration is too low, the initial capacity is low and it is difficult to meet the standard requirements. If it exceeds 35%, the battery open circuit voltage is too high, which seriously affects the battery life. It is usually in the range of 31% to 35%. This invention takes a concentration of 32% as an example:

[0051] The concentration of the prepared electrolyte is required to be 32%, the weight is 100kg, and concentrated sulfuric acid with a mass fraction of 51% is used as the mother solution of sulfate. 62.75kg of mother acid is weighed. The amount of pure water required is calculated as follows:

[0052] 100kg-62.75kg=37.25kg;

[0053] Divide the pure water into two parts, one part is 29.80kg, that is, 37.25kg×0.8=29.80kg;

[0054] The remaining weight is: 37.25kg-29.80kg=7.45kg;

[0055] Slowly pour 62.75 kg of sulfuric acid mother liquor into 29.80 kg of pure water, stir evenly, and cool at room temperature for use.

[0056] According to different battery designs, different formulas are selected. Calculate based on 100kg, weigh the additive (surfactant), add the amount of 0.05%~0.20%, add the additive to 7.45kg pure water, stir evenly until all the additives are dissolved, and then pour into dilute sulfuric acid that has been cooled to room temperature.

[0057] Based on 100kg, weigh anhydrous sodium sulfate (inorganic salt) and add 0.5%~1.0% to dilute sulfuric acid. Stir evenly and the electrolyte is ready.

[0058] Place the electrolyte in a low temperature box and cool it to 0℃~5℃ for use.

[0059] Example 1

[0060] According to the above configuration method, different electrolyte formulas are designed respectively, the additive is one of sodium dodecyl sulfate or sodium dodecylbenzene sulfonate or a mixture of the two, the inorganic salt additive is anhydrous sodium sulfate, and in the formation stage, the voltage usually reaches about 16.5V during the formation process, and the voltage can be controlled not to exceed 16.5V. If the electrolyte bubbles and a large amount of foam flows out, it proves that the electrolyte formula is not desirable, as shown in Table 1 below.

[0061] Table 1

[0062] Solution No. Anhydrous sodium sulfate Sodium Lauryl Sulfate Sodium dodecylbenzenesulfonate Availability 1 0.40% 0.04% / no 2 0.40% 0.05% / no 3 0.40% 0.15% / no 4 0.40% 0.18% / no 5 0.40% 0.20% / no 6 0.40% 0.25% / no 7 0.40% / 0.04% no 8 0.40% / 0.05% no 9 0.40% / 0.15% no 10 0.40% / 0.18% no 11 0.40% / 0.20% no 12 0.40% / 0.25% no 13 0.50% 0.04% / yes 14 0.50% 0.05% / yes 15 0.50% 0.15% / yes 16 0.50% 0.18% / yes 17 0.50% 0.20% / yes 18 0.50% 0.25% / no 19 0.50% / 0.04% yes 20 0.50% / 0.05% yes 21 0.50% / 0.15% yes 22 0.50% / 0.18% yes 23 0.50% / 0.20% yes 24 0.50% / 0.25% no 25 1.00% 0.04% / yes 26 1.00% 0.05% / yes 27 1.00% 0.15% / yes 28 1.00% 0.18% / yes 29 1.00% 0.20% / yes 30 1.00% 0.25% / no 31 1.00% / 0.04% yes 32 1.00% / 0.05% yes 33 1.00% / 0.15% yes 34 1.00% / 0.18% yes 35 1.00% / 0.20% yes 36 1.00% / 0.25% no 37 1.20% 0.04% / no 38 1.20% 0.05% / no 39 1.20% 0.15% / no 40 1.20% 0.18% / no 41 1.20% 0.20% / no 42 1.20% 0.25% / no 43 1.20% / 0.04% no 44 1.20% / 0.05% no 45 1.20% / 0.15% no 46 1.20% / 0.18% no 47 1.20% / 0.20% no 48 1.20% / 0.25% no 49 0.50% 0.05% 0.05% yes 50 0.50% 0.06% 0.04% yes 51 0.50% 0.04% 0.06% yes 52 1.00% 0.05% 0.05% yes 53 1.00% 0.06% 0.04% yes 54 1.00% 0.04% 0.06% yes 55 0.50% 0.075% 0.075% yes 56 0.50% 0.09% 0.06% yes 57 0.50% 0.06% 0.09% yes 58 1.00% 0.075% 0.075% yes 59 1.00% 0.09% 0.06% yes 60 1.00% 0.06% 0.09% yes 61 0.50% 0.10% 0.10% yes 62 0.50% 0.12% 0.08% yes 63 0.50% 0.08% 0.12% yes 64 1.00% 0.10% 0.10% yes 65 1.00% 0.12% 0.08% yes 66 1.00% 0.08% 0.12% yes 67 1.20% 0.125% 0.125% no 68 1.20% 0.15% 0.10% no 69 1.20% 0.10% 0.15% no 70 1.20% 0.125% 0.125% no 71 1.20% 0.15% 0.10% no 72 1.20% 0.10% 0.15% no

[0063] From the usable conditions in Table 1, when the addition amount of anhydrous sodium sulfate is less than 0.50% or exceeds 1.0%, it is easy to foam regardless of whether sodium dodecyl sulfate or sodium dodecylbenzene sulfonate is added alone or in combination.

[0064] Control the amount of anhydrous sodium sulfate added within the range of 0.5% to 1.0%. Sodium dodecyl sulfate or sodium dodecylbenzene sulfonate, added alone or in combination, should not exceed a total amount of 0.20%.

[0065] Example 2

[0066] A type battery was selected as the experimental battery, with a plate height of 120 mm, a distance between the positive and negative plates of 0.885 mm, and a separator thickness of 0.48 mm (100 kPa).

[0067] The electrolyte formula available in Example 1 was selected for experiments, and the battery was dissected at 0 cycles (i.e., initial state), 100 cycles, 300 cycles, and end of life. The dissection requirement was that the standing time should not exceed 10 minutes after full charge. After the dissection, the partition was cut into three parts in equal proportion along the height direction, namely the upper part, the middle part, and the lower part, and acid extrusion, filtration, and chemical titration were performed separately to test the mass fraction of sulfuric acid in the electrolyte. The stratification of the electrolyte was reflected by the extreme difference values ​​of the upper, middle, and lower parts. At the same time, the partition at the end of life was selected, washed and dried, and then characterized by SEM to measure the size of the lead sulfate particles. The larger the grain size, the higher the probability of short circuit.

[0068] Semi-finished batteries from the same batch were selected as comparison samples, and only sodium sulfate was added to the electrolyte.

[0069] Table 2

[0070]

[0071] From the results in Table 2, it can be seen that the amount of surfactant added is not less than 0.15%, and the effect of mixed addition of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate is better than adding them separately. When added in mixture, the mass proportion of sodium dodecyl sulfate exceeds 50%, which has a better effect.

[0072] Continuing to increase the addition amount to 0.20%, the effect will be better, but at the same time the manufacturing cost will increase.

[0073] Example 3

[0074] Battery B was selected as the experimental battery. A and B were of the same type of shell, designed with different capacities and different plate heights. The plate height of battery B was 100 mm, the distance between the positive and negative plates was 0.885 mm, and the selected separator thickness was 0.48 mm (100 kPa).

[0075] The electrolyte formula available in Example 1 was selected for experiments, and the battery was dissected at 0 cycles (i.e., initial state), 100 cycles, 300 cycles, and end of life. The dissection requirement was that the standing time should not exceed 10 minutes after full charge. After the dissection, the partition was cut into three parts in equal proportion along the height direction, namely, the upper part, the middle part, and the lower part. Acid extrusion, filtration, and chemical titration were performed separately to test the mass fraction of sulfuric acid in the electrolyte. The stratification of the electrolyte was reflected by the extreme difference values ​​of the upper, middle, and lower parts. At the same time, the partition at the end of life was selected, washed and dried, and then characterized by SEM to measure the size of the lead sulfate particles. The larger the grain size, the higher the probability of short circuit.

[0076] Semi-finished batteries from the same batch were selected as comparison samples, and only sodium sulfate was added to the electrolyte.

[0077] Table 3

[0078]

[0079] Among them, the lead dendrite diagrams in the AGM separators of batteries No. 9 and No. 14 are shown as follows: Figure 1 and Figure 2 Combined with the data in Table 3, Figure 1 It can be seen that the grain size is about 3μm, which is much smaller than the control sample (in this embodiment, battery numbers 1 and 2), so it is obviously improved. In this embodiment, batteries No. 3 to 10 are added with sodium dodecyl sulfate or sodium dodecylbenzene sulfonate alone. With the increase of surfactant, the size of lead dendrites gradually decreases. When the addition amount reaches 0.15%, the grain size will reach about 3μm if the addition amount continues to increase. Figure 2According to the results in Table 3, for batteries No. 11 to 20, mixed surfactants were selected for addition. From No. 11 to 12, it can be seen that when the total amount of mixed surfactant added does not exceed 0.10%, the grain size is greater than 12 μm. For No. 13 to 14, when the total amount of mixed surfactant added is 0.10%, the grain becomes smaller, and as the addition ratio of sodium dodecyl sulfate in the mixed surfactant increases, the grain size gradually becomes smaller.

[0080] From the above results, it can be seen that when the addition amount of surfactant is in the range of 0.10%~0.15%, the effect is relatively ideal and is significantly better than the control sample. When the addition amount reaches 0.15%, the effect is not further improved if the addition amount is continued to increase.

[0081] In addition, the effect of mixed addition of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate is better than adding them separately. When added in mixture, the effect is better when the mass proportion of sodium dodecyl sulfate exceeds 50%.

[0082] Example 4

[0083] Battery C was selected as the experimental battery. A, B, and C were of the same type of shells, designed with different capacities. Battery C had a plate height of 120 mm, the same as battery A, a distance between the positive and negative plates of 0.980 mm, and a separator thickness of 0.52 mm (100 kPa).

[0084] An available electrolyte formula was selected for experiments, and battery dissection was performed at 0 cycles (i.e., initial state), 100 cycles, 300 cycles, and end of life. The dissection requirement was that the standing time should not exceed 10 minutes after full charge. After dissection, the partition was cut into three parts in equal proportion along the height direction, namely the upper, middle, and lower parts. Acid extrusion, filtration, and chemical titration were performed separately to test the mass fraction of sulfuric acid in the electrolyte. The extreme difference between the upper, middle, and lower parts was used to reflect the stratification of the electrolyte. At the same time, the partition at the end of life was selected, washed and dried, and then characterized by SEM to measure the size of the lead sulfate particles. The larger the grain size, the higher the probability of short circuit.

[0085] Semi-finished batteries from the same batch were selected as comparison samples, and only sodium sulfate was added to the electrolyte.

[0086] Table 4

[0087]

[0088] Among them, the lead dendrite diagrams in the AGM separators of batteries No. 1 and 7 are shown as follows: Figure 3 and Figure 4As shown, battery No. 1 is a comparative sample, and only inorganic salts are added. It can be seen that the grain size exceeds 14μm, and the battery is prone to short circuit; battery No. 7, by adding sodium dodecylbenzene sulfonate alone, the proportion of inorganic salts is also increased, and the grain size is significantly reduced. From the results in Table 4 above, the effect is relatively ideal when the addition amount of surfactant is in the range of 0.15%~0.18%, which is obviously better than the comparative sample. When the addition amount reaches 0.18%, the effect is not further improved if the addition amount is further increased.

[0089] In addition, the effect of mixed addition of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate is better than adding them separately. When added in mixture, the effect is better when the mass proportion of sodium dodecyl sulfate exceeds 50%.

[0090] Example 5

[0091] Battery D was selected as the experimental battery. A, B, C, and D were of the same type of shells, designed with different capacities. Battery D had a plate height of 100 mm, the same as battery B, a distance between the positive and negative plates of 0.980 mm, and a separator thickness of 0.52 mm (100 kPa).

[0092] An available electrolyte formula was selected for experiments, and battery dissection was performed at 0 cycles (i.e., initial state), 100 cycles, 300 cycles, and end of life. The dissection requirement was that the standing time should not exceed 10 minutes after full charge. After dissection, the partition was cut into three parts in equal proportion along the height direction, namely the upper, middle, and lower parts. Acid extrusion, filtration, and chemical titration were performed separately to test the mass fraction of sulfuric acid in the electrolyte. The extreme difference between the upper, middle, and lower parts was used to reflect the stratification of the electrolyte. At the same time, the partition at the end of life was selected, washed and dried, and then characterized by SEM to measure the size of the lead sulfate particles. The larger the grain size, the higher the probability of short circuit.

[0093] Semi-finished batteries from the same batch were selected as comparison samples, and only sodium sulfate was added to the electrolyte.

[0094] Table 5

[0095]

[0096] Among them, the lead dendrite diagrams in the AGM separators of batteries No. 4 and 7 are shown as follows: Figure 5 and Figure 6As shown, by adding 0.05% sodium dodecyl sulfate to the inorganic salt additive, the No. 4 battery can be compared with the No. 1 battery, and it can be seen that the grain size is reduced to 4μm, indicating that the growth of the grain size is significantly slowed down; by adding 0.04% sodium dodecylbenzene sulfonate to the inorganic salt additive, the No. 7 battery can be compared with the No. 2 battery, and it can be seen that the grain size is reduced to 7μm, indicating that the growth of the grain size is significantly slowed down. From the results in Table 5 above, the effect is relatively ideal when the addition amount of surfactant is within the range of 0.05%~0.10%, which is significantly better than the control sample. When the addition amount reaches 0.10%, the effect is not further improved if the addition amount is further increased.

[0097] In addition, the effect of mixed addition of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate is better than adding them separately. When added in mixture, the effect is better when the mass proportion of sodium dodecyl sulfate exceeds 50%.

Claims

1. Application of an electrolyte for a lead-acid battery in the preparation of a lead-acid battery, wherein the electrolyte for a lead-acid battery comprises sulfuric acid and an additive, wherein the additive comprises the following raw materials, based on the mass of the sulfuric acid: 0.5% to 1.0% of an inorganic salt and 0.04% to 0.20% of a surfactant; in, The inorganic salt is anhydrous sodium sulfate, and the surfactant is at least one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; When the separator thickness of the lead-acid battery is h<0.5mm, the added amount of the surfactant is not less than 0.1%; when the separator thickness of the lead-acid battery is h≥0.5mm, the added amount of the surfactant is not higher than 0.18%.

2. The use according to claim 1, characterized in that: The plate height is recorded as H, and the distance between the positive and negative plates is recorded as L. When the thickness of the separator of the lead-acid battery is h<0.5mm, when H / L>120, the added amount of the surfactant is not less than 0.15%; when H / L≤120, the added amount of the surfactant is less than 0.15%; When the separator thickness of the lead-acid battery is h≥0.5mm, when H / L>120, the added amount of the surfactant is 0.15%~0.18%; when H / L≤120, the added amount of the surfactant is 0.05%~0.10%.

3. The use according to claim 2, characterized in that: The method for preparing the lead-acid battery electrolyte comprises the following steps: Sulfuric acid used in preparing the chemical composition; The surfactant is added according to the separator thickness of the lead-acid battery, the plate surface height and the distance between the positive and negative plates, and then added into the prepared sulfuric acid, and then the inorganic salt is added to obtain the lead-acid battery electrolyte.

4. The use according to claim 1, characterized in that: When preparing lead-acid batteries, the resulting voltage does not exceed 16.5V.

5. The use according to claim 1, characterized in that: The mass fraction of the sulfuric acid is 31% to 35%.

6. The use according to claim 1, characterized in that: When the surfactant is sodium dodecyl sulfate and sodium dodecylbenzene sulfonate, the mass ratio of sodium dodecyl sulfate to the surfactant is not less than 50%.

Citation Information

Patent Citations

  • Composition of electrolyte of lead storage battery

    KR1020090045483A